(untitled) (Al-Aasar, 2025)
Every man subliminally desires salvation and merely religion can accomplish this craving. Every religion enunciates salvation based on different conditions and limitations. Islam, being a divine faith, and the Qur’ān being a final revealed message not only enucleates the former scriptures but also disillusions misunderstandings in them. So, the Islamic concept of salvation is based on apocalyptical doctrines, not on delusional thoughts. Some scholars have no conception of Qur’ānic teachings so they raise objections to the Islamic concept of salvation. Sulṭān Paul is one of such contestants. He was born in Afghanistan from there his family migrated to Delhi, India, where he got Islamic education. In 1903, during a meeting in St. Paul’s Church in Bombay, he converted to Christianity. After conversion, he raised a lot of questions about the truisms of Islam, and the concept of salvation is one of them. To justify his assertion he utilized Islamic sources, Qur’ān and Ḥadīth but ignored the Bible which describes the same idea that Sulṭān Paul cast away. This short article provides a critical review of Sulṭān’s allegations regarding the Islamic concept of salvation so that the readers may know the facts.